(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Groundwater is the main source of water supply in areas in Nigeria including the research area. The research is aimed at delineating groundwater potentials in Ganye and environs using Dar Zarrouk parameters. Fourteen (14) vertical electrical soundings were conducted across the study area in order to determine Dar Zarrouk parameters to determine groundwater potentials in Ganye and environs. The area is underlain by migmatite-gneiss and Pan African granites. Weathered/fractured basement constitute the aquifer type in the area. The aquifer conductivity in the study area range between 0.00871 to 0.032032 ?-1 with mean value of 0.019493 ?-1. The aquifer longitudinal conductance ranges between 0.22246 to 0.759252 with mean value of 0.432846. The transverse resistance range between 627.8721 to 1,857.282 ?m2 with average value of 1,235.854 ?m2. The aquifer hydraulic conductivity range between 6.9314 to 15.562 m/day with mean value of 9.738 m/day while the transmissivity across the study area range between 114.2152 to 378.774 m2/day with mean value of 216.0487 m2/day.